2020
DOI: 10.3390/nano10071395
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogenic and Precipitated Amorphous Silica Nanoparticles Differentially Affect Cell Responses to LPS in Human Macrophages

Abstract: Previous work has demonstrated that precipitated (NM-200) and pyrogenic (NM-203) Amorphous Silica Nanoparticles (ASNPs) elicit the inflammatory activation of murine macrophages, with more pronounced effects observed with NM-203. Here, we compare the effects of low doses of NM-200 and NM-203 on human macrophage-like THP-1 cells, assessing how the pre-exposure to these nanomaterials affects the cell response to lipopolysaccharide (LPS). Cell viability was affected by NM-203, but not by NM-200, and only in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…However, for most SAS, the half maximal effective concentration (EC50) for several endpoints is comparatively low under protein-free conditions (e.g., 10–20 µg/mL for the release of LDH) [ 18 ], a finding which does not correspond to the in vivo effects of SAS especially when effects of amorphous and crystalline silica are compared [ 12 ]. On the other hand, the bioactivity of SAS in vitro is strongly reduced when particles (i) are administered in the presence of serum [ 20 ], (ii) are protein-treated prior to exposure [ 21 , 22 , 23 , 24 ] or (iii) are dispersed by extensive ultrasonic energy in the presence of low concentrations of albumin [ 25 ]. All aforementioned protein-treatments inevitably lead to the formation of a protein corona [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, for most SAS, the half maximal effective concentration (EC50) for several endpoints is comparatively low under protein-free conditions (e.g., 10–20 µg/mL for the release of LDH) [ 18 ], a finding which does not correspond to the in vivo effects of SAS especially when effects of amorphous and crystalline silica are compared [ 12 ]. On the other hand, the bioactivity of SAS in vitro is strongly reduced when particles (i) are administered in the presence of serum [ 20 ], (ii) are protein-treated prior to exposure [ 21 , 22 , 23 , 24 ] or (iii) are dispersed by extensive ultrasonic energy in the presence of low concentrations of albumin [ 25 ]. All aforementioned protein-treatments inevitably lead to the formation of a protein corona [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ASNPs potentiate activation by LPS, at least in terms of NO production, of murine macrophage Raw 264.7 cells [17]. More recently, we have shown that exposure to low doses of ASNP interferes with the induction of glutamine synthetase, a change potentially related to macrophage polarization [18], and delays IL-1β secretion in LPS-treated THP-1 human macrophage-like cells [19]. In both cases, pyrogenic NM-203 ASNPs produced larger effects than the precipitated NM-200 ASNPs, confirming their higher bioreactivity observed in studies with other cell models [17,19].…”
Section: Introductionmentioning
confidence: 88%
“…More recently, we have shown that exposure to low doses of ASNP interferes with the induction of glutamine synthetase, a change potentially related to macrophage polarization [18], and delays IL-1β secretion in LPS-treated THP-1 human macrophage-like cells [19]. In both cases, pyrogenic NM-203 ASNPs produced larger effects than the precipitated NM-200 ASNPs, confirming their higher bioreactivity observed in studies with other cell models [17,19]. These data suggest that the interaction of ASNP with innate immune cells may have more complex effects than pro-inflammatory activation, such as alterations in the time course and features of the cell response to LPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on those differences it is assumed that pyrogenic SAS causes the highest toxicity (van Kesteren et al 2015). This is strengthened by in vitro studies demonstrating a more pronounced effect for pyrogenic SAS compared to precipitated SAS (Bianchi et al 2020). But surface modification or changes in shape may also affect toxicokinetic behavior and toxicity.…”
Section: Silica Usedmentioning
confidence: 99%